Peer review of the pesticide risk assessment of the active substance benthiavalicarb (variant assessed benthiavalicarb‐isopropyl). (27th September 2021) - ,; Alvarez, Fernando; Arena, Maria; Auteri, Domenica; Borroto, Jorge; Brancato, Alba; Carrasco Cabrera, Luis; Castoldi, Anna Federica; Chiusolo, Arianna; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; et al.
Abstract: The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Poland, and co‐rapporteur Member State, France, for the pesticide active substance benthiavalicarb (variant assessed benthiavalicarb‐isopropyl) are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative use of benthiavalicarb‐isopropyl as a fungicide on potato (field use). The peer review also provided considerations on whether exposure to humans and the environment from the representative uses of benthiavalicarb‐isopropyl can be considered negligible, taking into account the European Commission's draft guidance on this topic. The reliable end points, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified. An evaluation of data concerning the necessity of benthiavalicarb‐isopropyl as a fungicide to control a serious danger to plant health which cannot be contained by other available means, including non‐chemical methods, is also presented.